Lactuca anatolica (Asteraceae: Lactucinae), a new species from eastern Anatolia (Turkey) - Behçet Lütfi̇; Yapar, Yakup (Phytotaxa, 2020)
Lactuca anatolica is described as a new species from the province of Bingöl, and is known from only one locality. Its diagnostic characters are discussed, and taxonomic comments are presented. Lactuca anatolica is similar to L. leucoclada, L. orientalis subsp. nuristanica and L. orientalis subsp. orientalis but differs from these species in achenes, indumentum and leaves. Its achenes were investigated using scanning electron microscopy (SEM). Data on ecology and IUCN conservation status of the new species are also presented. A distribution map of the new and related species is provided.